2017
DOI: 10.15296/ijwhr.2018.45
|View full text |Cite
|
Sign up to set email alerts
|

Related Factors of Domestic Violence: A Population-Based Research on Iranian Women

Abstract: Introduction The World Health Organization (WHO) defined domestic violence as "the range of physically, psychologically and sexually coercive acts used against adult and adolescent women by current or former male intimate partners" (1). Domestic violence is an important health problem in the countries, which devastates the configuration of communities and threatens the individual's life, health and happiness (2,3) Therefore, evaluation of the association between the different types of domestic violence and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…This study showed a high prevalence of lifetime IPV (58.5%) against women. This prevalence is similar to that reported in Erbil city of the Kurdistan, Iraq [6], in Salvador [7], among Iranian women [8] and in Pakistan [4]. This high and nearly similar prevalence of violence in these societies may be due to similar cultural and religious factors.…”
Section: Lifetime Violencesupporting
confidence: 85%
“…This study showed a high prevalence of lifetime IPV (58.5%) against women. This prevalence is similar to that reported in Erbil city of the Kurdistan, Iraq [6], in Salvador [7], among Iranian women [8] and in Pakistan [4]. This high and nearly similar prevalence of violence in these societies may be due to similar cultural and religious factors.…”
Section: Lifetime Violencesupporting
confidence: 85%
“…The STROBE checklist divides studies into three levels, including weak, moderate, and strong [27, 28]. Studies that have obtained 70% of the checklist score [15] are included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Postpartum sexual function is an important issue for couples, since the first postpartum sex is an important step for couples to establish sincere relationships [15]. Childbirth leads to anatomical and functional changes in the pelvic floor (PF) muscles, which might be responsible for some of women’s complaints about sexual problems during the postpartum period [6].…”
Section: Introductionmentioning
confidence: 99%
“…Poverty or unemployment, housekeeping, harmful drug and drink usage such as alcohol by the husband, the interference of others in the private lives of couples, the dissatisfaction with sexual expectations (16), the lack of women's employment, women's financial dependence on their husband, low literacy, low socioeconomic status, a history of husband's mental illness, and smoking (by 6.5 times) are highlighted as several factors which affect violence (17). Likewise, there is a meaningful relationship between husband's age, marital duration, family income, female's financial dependency, the level of female occupation, female job, husband's addiction, sexual satisfaction, and IPV (18). Violence in low social classes is high and often of physical type.…”
mentioning
confidence: 99%